A comprehensive geriatric assessment screening questionnaire (CGA‐GOLD) for older people undergoing treatment for cancer. (1st May 2016) - Whittle, A.K.; Kalsi, T.; Babic‐Illman, G.; Wang, Y.; Fields, P.; Ross, P.J.; Maisey, N.R.; Hughes, S.; Kwan, W.; Harari, D.
Abstract : Oncology services do not routinely assess broader needs of older people with cancer. This study evaluates a comprehensive geriatric assessment and comorbidity screening questionnaire (CGA‐GOLD) covering evidence‐based domains and quality of life (EORTC‐QLQ‐C30). Patients aged 65+ attending oncology services were recruited into (1) Observational cohort (completed CGA‐GOLD, received standard oncology care), (2) Intervention cohort (responses categorised 'low‐risk', 'high‐risk', 'possible need' by geriatricians). N  = 417 observational patients (1002 invited by post, 418 consented, age 73.9 ± 5.4) completed CGA‐GOLD in 11.7 ± 7.9 min, 86.3% required no assistance, 3.1% overall missing responses. Multiple problems reported: hypertension (18.1%), diabetes (16.9%), dyspnoea on flat surfaces (27.6%), polypharmacy (46%), difficulty walking (14.9%), fatigue (40.5%), living alone (30.9%), social isolation (11.2%), recent functional dependence (27.8%), urinary incontinence (21.4%), falls (13.3%). 237/239 intervention patients completed CGA‐GOLD and consecutive subsets examined. The doctor and nurse specialist independently identified same need level in 87.3% (high inter‐rater reliability kappa = 0.80), taking 1–2 min per questionnaire. Need level remained unchanged following hospital notes review against responses in 90% (75/83). 'Possible need' patients were telephoned with change in 29% (16/55) to low‐risk and none to high‐risk, confirming high need was not being missed. CGA‐GOLD screening questionnaire was acceptable to older patients, feasibly administered in NHS cancer services, described comorbidities, CGA and QOL needs, and reliably identified higher risk patients requiring further input for optimal cancer treatment.